PELATIHAN PEMBUATAN GANTUNGAN POT BUNGA BAGI KELOPOK IBU-IBU RUMAH TANGGA DIDESA KARANGANYAR LAMPUNG SELATAN - Amnah Amnah; Nursiyanto Nursiyanto; Wasilah Wasilah (Politeknik Negeri Sriwijaya, 2021)
In Karanganyar village, many mothers are in productive age, and they have the ability to engage new knowledge. The mothers have free time in the afternoon, around 15.00 until just before sunset. They get together to chat freely. Sometimes, conversations are not good for themselves. Time is wasted without any benefit as this is a problem. It is because there is time with their relatively young age. On the other hand, their economic condition is not very good. It makes the Community Service team takes an opportunity to provide these mothers with training, mentoring, and implementation. It hopefully can help their economy. Providing skills in making hanging flower pot hangers is something new for mothers in Karanganyar village. It can certainly provide an interesting solution in helping their economy. Training will be given to women in Karanganyar village. In addition, this service will also find a place to sell the produced products (Partners). Thus, they do not hesitate to have succeeded in making various kinds of attractive pot hangers of various sizes with various patterns